Disarming Pseudomonas aeruginosa Virulence by the Inhibitory Action of 1,10-Phenanthroline-5,6-Dione-Based Compounds: Elastase B (LasB) as a Chemotherapeutic Target - Galdino, Anna Clara M.; Viganor, Lívia; de Castro, Alexandre A.; da Cunha, Elaine F. F.; Mello, Thaís P.; Mattos, Larissa M.; Pereira, Marcos D.; Hunt, Mary C.; O’Shaughnessy, Megan; Howe, Orla; Devereux, Michael; McCann, Malachy; et al. (Frontiers in Microbiology, 2019)
Elastase B (lasB) is a multifunctional metalloenzyme secreted by the gram-negative pathogen Pseudomonas aeruginosa, and this enzyme orchestrates several physiopathological events during bacteria-host interplays. LasB is considered to be a potential target for the development of an innovative chemotherapeutic approach, especially against multidrug-resistant strains. Recently, our group showed that 1,10-phenanthroline-5,6-dione (phendione), [Ag(phendione)2]ClO4 (Ag-phendione) and [Cu(phendione)3](ClO4)2.4H2O (Cu-phendione) had anti-P. aeruginosa action against both planktonic- and biofilm-growing cells. In the present work, we have evaluated the effects of these compounds on the (i) interaction with the lasB active site using in silico approaches, (ii) lasB proteolytic activity by using a specific fluorogenic peptide substrate, (iii) lasB gene expression by real time-polymerase chain reaction, (iv) lasB protein secretion by immunoblotting, (v) ability to block the damages induced by lasB on a monolayer of lung epithelial cells, and (vi) survivability of Galleria mellonella larvae after being challenged with purified lasB and lasB-rich bacterial secretions. Molecular docking analyses revealed that phendione and its Ag+ and Cu2+ complexes were able to interact with the amino acids forming the active site of lasB, particularly Cu-phendione which exhibited the most favorable interaction energy parameters. Additionally, the test compounds were effective inhibitors of lasB activity, blocking the in vitro cleavage of the peptide substrate, aminobenzyl-Ala-Gly-Leu-Ala-p-nitrobenzylamide, with Cu-phendione having the best inhibitory action (Ki = 90 nM). Treating living bacteria with a sub-inhibitory concentration (½×MIC value) of the test compounds caused a significant reduction in the expression of the lasB gene as well as its mature protein production/secretion. Further, Ag-phendione and Cu-phendione offered protective action for lung epithelial cells, reducing the A549 monolayer damage by approximately 32% and 42%, respectively. Interestingly, Cu-phendione mitigated the toxic effect of both purified lasB molecules and lasB-containing bacterial secretions in the in vivo model, increasing the survival time of G. mellonella larvae. Collectively, these data reinforce the concept of lasB being a veritable therapeutic target and phendione-based compounds (mainly Cu-phendione) being prospective anti-virulence drugs against P. aeruginosa.